2019
DOI: 10.1097/md.0000000000015463
|View full text |Cite
|
Sign up to set email alerts
|

Real-world database investigating the association between diabetes mellitus and herpes zoster in Taiwan

Abstract: Little evidence is available about the correlation between diabetes mellitus and herpes zoster in Taiwan. This study aimed to investigate the correlation between diabetes mellitus and herpes zoster in Taiwan. A population-based cohort study was conducted using the database of Taiwan National Health Insurance Program. There were 27,369 subjects aged 20 to 84 years with newly diagnosed diabetes mellitus from 2000 to 2012 as the diabetes mellitus group and 107,705 sex- and age-matched subjects without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Diabetes, malignancies, chronic kidney disease/uremia, chronic obstructive pulmonary disease, and peptic ulcer disease were all associated with a significantly higher risk of HZ than the general population in most studies (range of HRs: 1.17-8.46) [13,14,18,[20][21][22][23][24][25][26][27]. The potential association was weaker in persons with depression, psychiatric disease, hyperlipidemia, hypertension, as well as those post-general anesthesia (range of HRs: 1.11-1.29) [20,25,26,28,29]. Conversely, systemic steroid use in patients with psoriasis was associated with a significantly reduced risk of HZ (HR: 0.6, 95% CI: 0.44-0.81) [30], as was radical prostatectomy and hormone therapy in patients with prostate cancer (HR: 0.60, 95% CI: 0.44-0.81) [31].…”
Section: The Risk Of Hz In Patients With Other Co-morbiditiesmentioning
confidence: 94%
“…Diabetes, malignancies, chronic kidney disease/uremia, chronic obstructive pulmonary disease, and peptic ulcer disease were all associated with a significantly higher risk of HZ than the general population in most studies (range of HRs: 1.17-8.46) [13,14,18,[20][21][22][23][24][25][26][27]. The potential association was weaker in persons with depression, psychiatric disease, hyperlipidemia, hypertension, as well as those post-general anesthesia (range of HRs: 1.11-1.29) [20,25,26,28,29]. Conversely, systemic steroid use in patients with psoriasis was associated with a significantly reduced risk of HZ (HR: 0.6, 95% CI: 0.44-0.81) [30], as was radical prostatectomy and hormone therapy in patients with prostate cancer (HR: 0.60, 95% CI: 0.44-0.81) [31].…”
Section: The Risk Of Hz In Patients With Other Co-morbiditiesmentioning
confidence: 94%
“…Table 1 demonstrated that 5 eligible cohort studies met the inclusion criteria. [ 11 15 ] The incidence of herpes zoster in patients with diabetes mellitus varied greatly between studies, ranging from 2.11 per 1000 person-years to 9.38 per 1000 person-years. The overall incidence of herpes zoster in patients with diabetes mellitus was 7.22 per 1000 person-years.…”
Section: Resultsmentioning
confidence: 99%
“…Patients aged ≥65 in diabetes group had the highest incidence rate of herpes zoster (11.91 per 1000 person-years) (Table 2 ). [ 11 , 13 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations